Students’ Strategies in Taking TOEFL Listening Test - Aina Razmalia; Sofyan A Gani (Research in English and Education Journal, 2017)
English Department students, as a department at Syiah Kuala University, are expected to be able to answer TOEFL listening questions effectively since they have been studying English as their major subject and concentration. However, it was found that some students still have problems in TOEFL test, especially in part A of Listening Comprehension section. This study is carried out to analyze the students’ strategies in Listening of TOEFL test. Descriptive quantitative approach was applied. 31 students who are in semester 8 to 12 were chosen incidentally as the subjects of this study. Meanwhile, the object of this study was the students’ strategies in Listening Comprehension of TOEFL test. The writer used survey techniques in collecting the data. The data were collected by using questionnaire sheet as the instrument. The result showed that the strategies suggested by Phillips (2001) in part A of Listening in TOEFL test are implemented 69% by the students of English Department of Syiah Kuala University. To conclude, the students apply the strategies with the frequency of “sometimes”. Therefore, it is suggested that students implement more strategies, and teachers or instructors are recommended to motivate them and build their awareness to use more strategies when taking a TOEFL.